Democracy and Other Neoliberal Fantasies : Communicative Capitalism and Left Politics - Dean, Jodi, 1962- (Book collections on Project MUSE., 2009)
Democracy and Other Neoliberal Fantasies is an impassioned call for the realization of a progressive left politics in the United States. Through an assessment of the ideologies underlying contemporary political culture, Jodi Dean takes the left to task for its capitulations to conservatives and its failure to take responsibility for the extensive neoliberalization implemented during the Clinton presidency. She argues that the left's ability to develop and defend a collective vision of equality and solidarity has been undermined by the ascendance of "communicative capitalism," a constellation of consumerism, the privileging of the self over group interests, and the embrace of the language of victimization. As Dean explains, communicative capitalism is enabled and exacerbated by the Web and other networked communications media, which reduce political energies to the registration of opinion and the transmission of feelings. The result is a psychotic politics where certainty displaces credibility and the circulation of intense feeling trumps the exchange of reason.